Peranan Rekonsiliasi Bank dalam Meningkatkan Akurasi Laporan Keuangan PT Adhibaladika Agung - Celine Amanda Sarifatul Sabrina; Yolanda Maghdalena Sihaloho (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Bank reconciliation is one of the crucial internal control procedures in maintaining the accuracy of a company's financial statements. This study aims to analyze the role of bank reconciliation in improving the accuracy of PT Adhibaladika Agung's financial statements. The research method used is a descriptive qualitative approach with observation methods conducted during an internship in the accounting and finance division. The internship was conducted over a period of 5 months, from January 20, 2025, to June 20, 2025. In the reconciliation process, the main focus of this study was on cash transactions involving settlements from Electronic Data Capture (EDC), which were then matched with the Operational Report (OPR), summarized, and entered into Microsoft Excel. The results of the study indicate that bank reconciliation plays a very important role in identifying discrepancies between company records and bank statements, ensuring the completeness of transaction records, and enhancing the reliability of financial information. A systematic and regular reconciliation process can reduce the risk of recording errors, aid in the early detection of potential fraud, and improve transparency in financial reporting. This study provides practical contributions to PT Adhibaladika Agung in optimizing the bank reconciliation process as part of an effective internal control system.